In-depth proteomic profiling identifies potentiation of the LPS response by 7-ketocholesterol - Iain R. Phair; Magdalena Sovakova; Noor Alqurashi; Raid B. Nisr; Alison D. McNeilly; Douglas Lamont; Graham Rena (Journal of Molecular and Cellular Cardiology Plus)
In patients with stable coronary artery disease, plasma levels of 7-ketocholesterol (7-KC), found at high levels in atherosclerotic lesions, predict risk of incident heart failure dose dependently, potentially contributing to disease aetiology. Previous studies demonstrated that 7-KC can elicit effects on macrophage function; however, effects of 7-KC on the macrophage proteome have not been studied systematically. Here we used quantitative mass spectrometry to establish the effect of 7-KC on the mouse macrophage proteome. 7-KC independently mediated dynamic changes, including on atherogenic/M1 markers, cholesterol metabolism, biosynthesis and transport, as well as nutrient transport more broadly. These changes were however insufficient alone to drive changes in cytokine and chemokine secretion. Rather, they prime the macrophage, potentiating LPS-stimulated TNF alpha secretion and key pro-inflammatory enzymes. Our results indicate that 7-KC has independent metabolic effects on the macrophage; however, effects on the immune system are primarily due to the changes in metabolism priming the response to an inflammatory stimulus. Earlier findings from CANTOS and the recent FDA approval of colchicine highlight that inflammation is a viable target for cardiovascular disease; however, it is currrently unclear which will be the best anti-inflammatory targets to pursue in the future. In this context, our findings suggest that drugs targeting atherogenic markers induced by 7-KC might be well tolerated, as they will not necessarily be expected to be immunosuppressive.